PRAGMATICS IN EFL CLASSROOM: AVOIDING PRAGMATIC FAILURE IN CROSS-CULTURAL COMMUNICATION - Pamungkas, Nailul Author Restu; Wulandari, Lutfina Tarita (English Education:Journal of English Teaching and Research, 2020)
In teaching language along with its culture, teacher should take pragmatic aspects into consideration, since understanding pragmatics will help foreign language learners to avoid false interpretation which will cause misunderstanding in communication between speakers with different culture and social backgrounds. It is called as pragmatic failure which usually takes place in cross-cultural communication. Since pragmatics plays quite important role in communication, it is important for foreign language learners to have sensitivity of cross cultural pragmatics, which is commonly known as cross cultural or intercultural pragmatic awareness. However, teaching language along with culture seems to be problematic, since it is relatively difficult to choose which aspect(s) of culture to teach, what content to include, and to represent cultures implicitly under study which presents differences from the norm of students’ local culture. Therefore, this paper tries to explore the essential issues of spoken discourse, pragmatics, cross cultural pragmatics, pragmatic failure, pragmatic awareness, and its implication to pedagogy.